Acute and chronically increased immunoreactivity to phosphorylation-independent but not pathological TDP-43 after a single traumatic brain injury in humans - Johnson, Victoria E. (2011)
The pathologic phosphorylation and sub-cellular translocation of neuronal transactive response-DNA binding protein (TDP-43) was identified as the major disease protein in frontotemporal lobar degeneration (FTLD) with ubiquitinated inclusions, now termed FTLD-TDP, and amyotrophic lateral sclerosis (ALS). More recently, TDP-43 proteinopathy has been reported in dementia pugilistica or chronic traumatic encephalopathy caused by repetitive traumatic brain injury (TBI). While a single TBI has been linked to the development of Alzheimer’s disease and an increased frequency of neurofibrillary tangles, TDP-43 proteinopathy has not been examined with survival following a single TBI. Using immunohistochemistry specific for both pathological phosphorylated TDP-43 (p-TDP-43) and phosphorylation-independent TDP-43 (pi-TDP-43), we examined acute (n = 23: Survival < 2 weeks) and long-term (n = 39; 1–47 years survival) survivors of a single TBI versus age-matched controls (n = 47). Multiple regions were examined including the hippocampus, medial temporal lobe, cingulate gyrus, superior frontal gyrus and brainstem. No association was found between a history of single TBI and abnormally phosphorylated TDP-43 (p-TDP-43) inclusions. Specifically, just 3 of 62 TBI cases displayed p-TDP-43 pathology versus 2 of 47 control cases. However, while aggregates of p-TDP-43 were not increased acutely or long-term following TBI, immunoreactivity to phosphorylation-independent TDP-43 was commonly increased in the cytoplasm following TBI with both acute and long-term survival. Moreover, while single TBI can induce multiple long-term neurodegenerative changes, the absence of TDP-43 proteinopathy may indicate a fundamental difference in the processes induced following single TBI from those of repetitive TBI.